Emerging Ethical AI Governance in Southeast Asia through Global and Regional Frameworks - Numtip Smerchuar (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
Artificial intelligence (AI) has generated increasing governance and ethical concerns worldwide, including issues related to transparency, accountability, fairness, privacy, and human rights. In response, international organizations and governments have developed frameworks intended to promote responsible and ethical AI development. Within Southeast Asia, the Association of Southeast Asian Nations (ASEAN) introduced the ASEAN Guide on AI Governance and Ethics in 2024 as a regional framework to support ethical AI governance and policy coordination among member states. This study examines how global AI governance principles are translated into ASEAN’s regional framework and adapted within national AI governance strategies in Singapore, Vietnam, Indonesia, and Thailand. Using qualitative documentary analysis and a comparative case study approach, the study analyzes international, regional, and national AI governance frameworks through the lenses of global governance and norm diffusion. The findings indicate that ASEAN has emerged as an important platform for promoting ethical AI principles and regional policy coordination through a soft-governance approach. However, substantial variation exists in governance readiness, institutional capacity, and implementation across member states. While Singapore demonstrates a relatively advanced AI governance framework, Vietnam, Indonesia, and Thailand remain at different stages of policy development and implementation. The study further finds that global AI governance principles originating from frameworks such as UNESCO and the OECD are transmitted through ASEAN’s regional framework and selectively adapted within national governance systems. Although ASEAN provides a common ethical foundation, its voluntary and non-binding nature limits its ability to ensure consistent implementation across the region. Strengthening regional coordination, institutional capacity, and implementation mechanisms will therefore be essential for advancing ethical AI governance in Southeast Asia.